Gojek and Brand Popularity: A Study of the Mediating Effect of Gojek’s Merger with Competitor - Sherisa, Livia Alma; Pangaribuan, Christian Haposan; Setiawan, Johan (APPS Publications, 2021)
Objective – To investigate consumer attitudes towards accepting Gojek’s merger with competitor and the effects on Gojek’s brand popularity.Methodology – This research uses quantitative method distributed to Gojek’s active users (n=506) in Indonesia through an online survey platform. The data was analyzed using multiple linear regression.Findings – The variables attachment to Gojek, satisfaction with Gojek, and acceptance of Gojek’s merger with competitors were significant contributors to the dependent variable brand popularity of Gojek. Meanwhile, word-of-mouth about Gojek and perceived fairness of Gojek price do not have significant relationships with brand popularity of Gojek. For the dependent variable acceptance of Gojek’s merger with a competitor, word-of-mouth about Gojek and attachment to Gojek were significant contributors. At the same time, perceived fairness of Gojek price and satisfaction with Gojek were not significant contributors.Novelty – This research provides an insight into brand popularity of Gojek services in Indonesia and the influence of the acceptance of Gojek’s merger with competitor.